2008
DOI: 10.1097/cmr.0b013e32830b3536
|View full text |Cite
|
Sign up to set email alerts
|

Research on the antitumor effect of ginsenoside Rg3 in B16 melanoma cells

Abstract: Ginsenoside Rg3 is an effective chemical component extracted from the red Panix. The experiment demonstrated that it might effectively inhibit proliferation and metastasis of tumor cells. The exact molecular mechanism of Rg3 remains unclear so far. To further explore the antitumor function of Rg3, we investigated the in-vitro and in-vivo activity of Rg3 in the treatment of B16 melanoma cells, derived from C57BL/6 mouse, capable of forming tumor colonies in the lungs following intravenous injection. Cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 21 publications
1
62
0
Order By: Relevance
“…We speculate that Rg3 may have antitumor effects in human hepatocellular carcinoma by inhibiting cancer cell growth. This result is consistent with previous studies on the anticarcinogenic effects Rg3 in other malignant tumors (7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionsupporting
confidence: 83%
“…We speculate that Rg3 may have antitumor effects in human hepatocellular carcinoma by inhibiting cancer cell growth. This result is consistent with previous studies on the anticarcinogenic effects Rg3 in other malignant tumors (7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionsupporting
confidence: 83%
“…Nuclear staining with Hoechst 33258 was performed as previously described (Cheah et al, 2006;Chen et al, 2008). Briefly, treated and untreated cells were washed with phosphate buffered saline (PBS) followed by incubation in 10 µg/mL Hoechst 33258 solution at room temperature for 20 min.…”
Section: Nuclear Staining With Hoechst 33258mentioning
confidence: 99%
“…Ginsenoside Rg3 inhibits angiogenesis of Lewis lung carcinoma [7,8] , metastasis of intestinal adenocarcinomas and B16 melenoma [9,10] , and proliferation of prostate cancer cells [11,12] . Recent reports showed that tanshinone II-A, an alcohol extract of the root of Salvia miltiorrhiza Bunge, could reverse malignant phenotypes and inhibit the growth of CRC and hepatocarcinoma cells [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%